PENGEMBANGAN MEDIA BIG BOOK BERBASIS DONGENG SUMATERA SELATAN PADA ANAK KELOMPOK B DI PAUD PEMBINA NIBUNG - anita, anita - (Universitas sriwijaya, 2018)
This development research aims to create a big book based media fairy tale South Sumatra in children group B in PAUD Pembina Nibung. This development uses a combination of Rowntree's development model and Tessmer's evaluation. The Rowntree development model consists of three stages, namely the planning stage, the development stage and the evaluation phase. During the evaluation phase, formative evaluation was proposed by Tessmer consisting of 5 stages, namely selt evaluation, expert review, one-to-one evaluation, small group evaluation and field test. Data collection techniques using walkthrough and observation. The result of data analysis shows that in the evaluation of expert review stage, the average percentage of the assessment results from experts on big book 1, big book 2 and big book 3 is 3, 96 (very valid category). Phase one to one evaluation obtained the average results of observations of children from big book 1, big book 2 and big book 3 for 94.7 (Good One category). The small group evaluation stage shows the average observation on big book 1, big book 2 and big book 3 of 97.3 (very good category). In the field test stage got the observation value with big book 1, big book 2 and big book 3 of 96 (excellent category). From all stages that have been done then it can be concluded that the big book based media fairy tales of South Sumatra declared valid, practical, and effective develop potential effects for children.